Glycerol as an Energy Source for Ruminants: A Meta-Analysis of in Vitro Experiments - T. M. Syahniar; M. Ridla; A. A. Samsudin; A. Jayanegara (Faculty of Animal Science, Bogor Agricultural University, 2016)
Glycerol or glycerin is generally recognized as a safe compound to be used in animal feed, especially for ruminants. A number of in vitro studies related to glycerol supplementation in ruminant ration have been published but to date the results have not been summarized. The objective of this study was, therefore, to evaluate in vitro digestibility, ruminal fermentation characteristics, total gas and methane production through the meta-analysis approach. Meta-analysis was applied to 13 experiments and 42 treatments dealing with glycerol supplementation in ruminants. Data were analyzed by general linear model procedure in which the glycerol levels and the different studies were treated as fixed effects. Results revealed that glycerol supplementation did not affect the in vitro digestibility and total VFA production, but significantly decreased molar proportion of acetate and iso-valerate (P<0.05). In contrast, molar proportion of propionate, butyrate, and valerate significantly increased, and thus the ratio of acetate to propionate declined linearly (P<0.05). Methane production decreased linearly and accompanied with an increase of total gas production with increasing levels of glycerol supplementation (P<0.05). It is concluded that the use of glycerol as an energy substitution in animal feed has no detrimental effects in the rumen and environmentally friendly.